2018
DOI: 10.1080/1828051x.2018.1450099
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofListeria monocytogenesby a formulation of selected dairy starter cultures and probiotics in anin vitromodel

Abstract: Three strains of lactic acid bacteria (LAB) and a commercial probiotic were selected to evaluate their in vitro activity towards Listeria monocytogenes. The strains Lactococcus lactis ssp. lactis, strain 340, L. lactis ssp. lactis, strain 16; Lactobacillus casei ssp. casei, strain 208 and Enterococcus faecium UBEF-41 were inoculated into skim milk and brain heart infusion broth (BHI) to get an initial Lactococcus: Lactobacillus: E. faecium UBEF-41 ratio of 2:1:1 and a concentration of approximately 7 log cfu m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…1). In fact, all strains were able to inhibit Listeria cells due to acid production (data not shown) which is in line with findings of Iulietto et al [53]. As the presence of E. coli was recorded on ripening day 21 in sample A, the strong inhibitory effect of the strains on E. coli 3014, with the percentage of survival lower than 20%, should be highlighted.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1). In fact, all strains were able to inhibit Listeria cells due to acid production (data not shown) which is in line with findings of Iulietto et al [53]. As the presence of E. coli was recorded on ripening day 21 in sample A, the strong inhibitory effect of the strains on E. coli 3014, with the percentage of survival lower than 20%, should be highlighted.…”
Section: Discussionsupporting
confidence: 90%
“…The nondissociated form of lactic acid induces intracellular pH decrease, thus causing collapse of the proton electrochemical gradient in susceptible bacteria, resulting in its bacteriostatic or bactericidal action. In addition, antimicrobial peptides bacteriocins are also commonly produced among Lactobacillus species with the antagonistic activity, mostly against phylogenetically related bacteria [11,[53][54][55][56]. Casaburi et al [57] isolated the bacteriocin-producing L. curvatus 54M16 strain considered to be an appropriate starter culture during fermented sausage ripening to improve the quality and safety of traditional fermented sausages prepared without the addition of antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that the minimum lactobacilli concentration required to reduce listerial growth in whole milk was 10 6 CFU ml −1 . Although the antilisterial activity of Lactobacillus strains has been previously reported in milk and other dairy products (Ehsani et al, ; Iulietto et al, ), the determination of the minimum concentration of lactobacilli required to reduce listerial growth in milk has not been previously studied. Our findings partially agreed with a previous report carried out by Pujato et al (), where the antilisterial effect of another LAB strain was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is very scarce information on the antilisterial activity produced by Lactobacillus spp. specifically tested in milk (Iulietto et al, ; Millette, Luquet, & Lacroix, ). In those few reports, lactobacilli strains, originally isolated from milk and dairy products, were conveniently evaluated in milk with low fat content to test their in situ antilisterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the growth dynamics of the pathogen, highlighted in the study, indicate that the sauce does not represent a favourable substrate for the development of the microorganism during the shelf-life at the tested storage temperatures (δ <0.5 log CFU/g) [10]. It could be supposed a competitive action against L. monocytogenes from the naturally present microbiota consisting of lactic acid bacteria and yeasts which can grow in the product during its shelf-life, as reported by numerous scientific studies [21][22][23][24].…”
Section: Inoculated Samplesmentioning
confidence: 94%